محددات قطاع الاستثمار بولاية كسلا - السودان خلال الفترة (2010-2017م) - الطاهر, موسى; موسى, المهدي; خوجلي, ابراهيم; عبد المطلب, عبد اللطيف (Université de M'sila, 2020)
مستخلص هدفت الدراسة لمعرفة محددات القطاع الاستثماري بولاية كسلا. اعتمدت الدراسة المنهج الوصفي التحليلي والمنهج المؤسسي. بنيت الدراسة على الفرض الرئيس التالي: ما هي محددات القطاع الاستثماري بولاية كسلا؟ توصلت الدراسة أن هنالك عوامل متعددة ومتداخلة يصعب معها الفصل والتحديد أسهمت بدرجات متفاوتة في محددات القطاع الاستثماري بولاية كسلا والذي تبدو أبرز مؤشراته في مجموعة الظروف الطبيعية والسياسية والاقتصادية والقانونية التنظيمية والاجتماعية والثقافية التي توثر بطريقة مباشرة او غير مباشرة سلبا أو إيجابا في بيئة النشاط الاستثماري بالولاية وقرارات المستثمرين التي أضعفت النشاط الاستثماري بالولاية. أوصت الدراسة بتطبيق منهج المرحلتين لتطوير وتشجيع الاستثمار المنهج الإقليمي ومنظومة العتبة الحدية البيئية لتخطي تلك العقبات فيما يتعلق بإزالة العقبات القطاع الاستثماري بالولاية الذي يودي بدوره إلي استقرار إنسان الولاية. Abstract The study aimed to know the determinants of the investment sector in Kassala State. The study was used the descriptive, analytical and institutional approach's. The study was based on the following main assumption: What were the determinants of investment sector in Kassala State? The study concluded that there were multiple and interrelated factors with which it is difficult to separate and specify contributed to various degrees in the determinants of investment sector in Kassala State, whose most prominent indicators appear in the group of natural, political, economic, legal, organizational, social and cultural conditions that affect, directly or indirectly, negatively or positively in the environment of investment activity in the state and decisions Investors weakened the state's investment activity. The study recommended apply the two-stage approach to developing and encouraging investment the regional approach and the environmental threshold system to overcome these obstacles with regard to removing obstacles in the state's investment sector, which in turn leads to the stability of the state's human being.
Keywords: Keywords: Determinants, Investment Sector, Investment map, Investment law, Kassala State. ; كلمات مفتاحية: محددات، القطاع الاستثماري، الخارطة الاستثمارية، قانون الاستثمار، ولاية كسلا.